PENINGKATAN KEMAMPUAN MENULIS PERMULAAN ANAK MELALUI MEDIA SAND PAPER ALPHABET DI KELOMPOK B TK NURSA BANDAR LAMPUNG - siti Kurniasih (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2020)
This study is aimed at exploring the writing ability improvement process of group B students in TK Nursa and investigating to what extend the processing result of writing ability can be improved through sand paper alphabet. This study was a classroom action research using Kemmis and Mc. Taggart research model. This study was conducted in 2 cycles with 6 meetings in each cycle where every cycle consisted of the following steps: planning, action and observation, reflection. The sample of this study was 12 Group B students comprissing of 5 male students and 7 female students. The instruments used in this study was observational sheet of students activities using sand paper alphabet. The data in this study were quantitative and qualitative data. Quantitative data were analyzed by using descriptive statistic to compare the result from the first and second cycle. While qualitative data from field notes and interview were analyzed through the following steps: data reduction, data display and data verification. The results of this study show that there is the improvement of writing ability through sand paper alphabet, proven by the writing ability mean score in pre-cycle which was 50,17 % improve to 67,15 % in cycle I and keep increasing becoming 76,04 % in cycle II.